Pygmy grasshoppers of the genus Xistra Bolívar, 1887 (Orthoptera: Tetrigidae: Metrodorinae) - Zhang, Rong-Jiao; Deng, Wei-An; Li, Jie-Juan; Lin, Li-Liang (Zootaxa, 2022)
The genus Xistra Bolívar is reviewed. Two new species from China, Xistra hainanensis Deng, sp. nov. and Xistra nigriabdominis Deng, sp. nov. are described and illustrated. Three new combinations are established: Xistra emeiensis (Zheng, 1998), comb. nov., Xistra guangxiensis (Zheng, 1998), comb. nov. and Xistra lochengensis (Zheng, 2005), comb. nov. Four new synonyms are established: Bannatettix ruiliensis Zheng, 1993 = Xistra klinnema Zheng & Zeng, 2011, syn. nov., Systolederus emeiensis Zheng, 1998 = Xistra yaanensis Zheng, 2009, syn. nov., Systolederus guangxiensis Zheng, 1998 = Xistra longzhouensis Zheng & Jiang, 1998, syn. nov., Mazarredia lochengensis Zheng, 2005 = Xistra oculata Li, Deng & Zheng, 2014, syn. nov. In addition, an updated key to all species of the genus Xistra is given.